2017
DOI: 10.1177/0363546517691950
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Revision Surgery After Superior Labral Anterior-Posterior Repair: A National Perspective

Abstract: Risk factors for revision surgery after SLAP repair include age >40 years, female sex, obesity, smoking, and diagnosis of biceps tendinitis or long head of the biceps tearing. The diagnosis of biceps tendinitis (OR, 3.5) or long head of the biceps tearing (OR, 5.1) at or before the time of surgery was an especially significant risk factor for revision surgery. The high cost of revision surgery highlights the importance of appropriate indications to avoid the need for subsequent procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 30 publications
(32 reference statements)
2
31
0
Order By: Relevance
“…However, this database has high selection bias because it is constructed from case logs of candidate orthopaedic surgeons sitting for the Part II examination. 30 Using the PearlDiver database, Taylor et al 35 found that age older than 40 years was a risk factor for revision surgery, along with female sex, obesity, smoking, and a concomitant diagnosis of biceps tendinitis at or before the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, this database has high selection bias because it is constructed from case logs of candidate orthopaedic surgeons sitting for the Part II examination. 30 Using the PearlDiver database, Taylor et al 35 found that age older than 40 years was a risk factor for revision surgery, along with female sex, obesity, smoking, and a concomitant diagnosis of biceps tendinitis at or before the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies to date have linked the outcomes of SLAP repair versus tenodesis to the patient’s age [ 22 , 23 , 25 - 27 , 35 , 41 , 61 , 69 ]. The cohort studies of Alpert et al [ 22 ] and Schrøder et al [ 35 ] documented in the long-term, patients older and younger than forty years of age perform as well in terms of functional scores and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the largest cohort studies (179 patients), albeit a military population, found the relative risk for failure to be 3.45 in patients older than 36 years of age [ 34 ]. Taylor et al [ 69 ] performed a database study that demonstrated age greater than 40 (OR 1.5), Female Sex (OR 1.5), obesity (OR 1.8), smoking (OR 2.0) were all significant risk factors for failure following SLAP repair. Frank et al [ 70 ] analysis of a 62 patient cohort found similar risk factors for failure of SLAP repairs including age, smoking, diabetes, high demand labor and concomitant biceps symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age has been found to be a risk factor for revisions, 40,47 as has concomitant diagnosis of biceps tendinitis or biceps tendon tear. 47 There are many possible underlying reasons for failed SLAP repair and revision surgery, including incorrect diagnosis, altered biomechanics, 13,27 hardware complications or prominent suture knots, 20,35,41,49,52,55 lack of healing, 43,52 and persistent pain, inflammation, and stiffness.…”
mentioning
confidence: 99%